PRINCIPLE AND EXPERIMENT SIMULATION OF THE TELESCOPIC CASING ANTI-SWING DEVICE OF OFFSHORE CRANE - HAN GuangDong; CHEN HaiQuan; SUN YuQing; ZHANG JinNan; WANG ShengHai (Jixie qiangdu)
For offshore crane in the operation process at sea,due to the suspension of lifting wire rope belongs to the flexible parts,also wind,wave and ocean environment to inflect the load. These cause the load swing. A new type of offshore crane telescopic sleeve stabilizer was proposed based on the work condition of crane at sea. It uses the casing of the rigid constraints to reduce the swing range of the load,and using the universal torque structure to reduce the stress of the casing. When the casing is moving through the universal torque structure. Rely on the spring dampers to store and release energy. By these methods to reduce the swing of load. The telescopic sleeve device was introduced. A mathematical model of the ship,crane and telescopic sleeve is established. The kinematics analysis of the simulation model is carried out by using Adams. Verify the obvious damping effects of the telescopic sleeve device. At the same time,through constructing the experimental platform for actual experiments,Verifying the telescopic sleeve device in the practical application of also has significant effect of damping.